Impeding fatal violence through third-party diplomacy: The effect of mediation on conflict intensity. (July 2021) - Ruhe, Constantin
Existing research provides no systematic insights into if and how mediation impedes battle-related deaths. Therefore, this article presents a temporally disaggregated analysis and assesses the effect of mediation on monthly fatal violence. The article predicts that adversaries evaluate opponents' trustworthiness from both fighting and negotiation behavior. It argues that reducing fighting intensity during negotiations is a sign of cooperation, which can be negotiated by mediators to build trust. Over the course of mediation, the content of negotiations provides information about how genuinely a conflict party is interested in conflict resolution. Only if mediation achieves negotiation of core incompatibilities will conflict parties be willing to reduce fighting intensity. Under these conditions, information revealed in a mediation process can build trust and substantively reduce violence. An empirical analysis of all African conflicts between 1993 and 2007 supports this prediction and shows that on average mediation is followed by substantive and lasting reductions in fatal violence, if mediation discusses the conflict's main incompatibility. In contrast, mediation on other topics is associated with a small, fleeting reduction in violence. Data of battle-related fatalities in Syria during negotiations as well as qualitative evidence further support the theoretical mechanism and the model prediction. The study concludes that mediation can reduce conflict intensity substantively, if it achieves exchange between conflict parties on the main conflict issues.